A model to evaluate Pauwels type III femoral neck fractures. (March 2018) - Magone, Kevin M; Owen, Jonas K; Kemker, Bernard P; Bloom, Oliver; Martin, Sidney; Atkinson, Patrick
While many femoral neck fractures can be reliably treated with surgical intervention, Pauwels III femoral neck fractures in the young adult population continue to be a challenging injury, and there is no consensus on optimal treatment. As such, there are past and ongoing biomechanical studies to evaluate the fixation provided by different constructs for this inherently unstable fracture. While many investigations rely on cadavers to evaluate the biomechanical performance of a construct, significant inter-subject variability can confound the analysis. Biomechanical femur analogs are being used more frequently due to more consistent mechanical properties; however, they have not been stringently evaluated for morphology or suitability for instrumentation. This study sought to determine the variability among composite femoral analogs as well as consistently create a Pauwels III injury and instrument the analogs without the need for fluoroscopic guidance. In total, 24 fourth-generation composite femoral analogs were evaluated for femoral height, neck–shaft angle, anteversion, and cortical thickness. A method was developed to simulate a Pauwels III fracture and to prepare three different constructs: an inverted triangle of cannulated screws, a sliding hip screw, and a hybrid inverted triangle with cannulated screws and a sliding hip screw. Radiographs were utilized to evaluate the variation in implant position. All but one of the morphological parameters varied by <1%. The tip-to-apex distance for all sliding hip screw hardware was 18.8 ± 3.3 mm, and all relevant cannulated screw distances were within 5 mm of the adjacent cortex. All screws were parallel, on average, within 1.5° on anterior–posterior and lateral films. Fourth-generation composite femora were found to be morphologically consistent, and it is possible to consistently instrument the analogs without the use of fluoroscopy. This analog and hardware implantation model could serve as a screening model for new fracture repair constructs without the need for cadaveric tissues or radiologic technology.